A Novel SERPINB1 Single-Nucleotide Polymorphism Associated With Glycemic Control and β-Cell Function in Egyptian Type 2 Diabetic Patients - Kassem, Dina H.; Adel, Aya; Sayed, Ghada H.; Kamal, Mohamed M. (Frontiers in Endocrinology, 2020)
Aims: Serine protease inhibitor B1 (SerpinB1) is a neutrophil elastase inhibitor that has been proved to be associated with type 2 diabetes mellitus and pancreatic β-cell proliferation. In this study, we investigated 2 SERPINB1 SNPs; rs114597282 and rs15286; regarding their association with diabetes risk, various anthropometric and biochemical parameters in Egyptian type 2 diabetic patients. Materials and Methods: A total of 160 subjects (62 control and 98 type 2 diabetic patients) participated in this study. Various anthropometric and biochemical parameters were assessed. Genotyping assay for the two SNPs was done using Taqman genotyping assays. The association of rs15286 variants with risk of diabetes, various biochemical parameters and glycemic control in diabetic patients was assessed. Results: All genotyped subjects were found to be homozygous TT for SERPINB1 rs114597282. All genotype variants of SERPINB1 rs15286 were found in our Egyptian subjects with A being the minor allele. The SNP rs15286 was not found to be associated with risk of diabetes. The AA genotype was found to be associated with lower fasting plasma glucose, lower HbA1c%, better β-cell function and glycemic control in diabetic patients. The G allele was associated with poor glycemic control. Conclusions: The genotypes AA, AG or GG of SERPINB1 gene SNP rs15286 are all represented in the studied sample , however, it is not associated with risk of diabetes. Genotype AA of SNP rs15286 is associated with better glycemic control and better β-cell function in diabetic patients, while G allele potentially represents the “risk allele” of poor glycemic control.